UNITY AND IDENTITY IN PERSPECTIVE OF THE FREE EVANGELICAL CHURCHES - HEISER, Andreas (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2018)
Free evangelical Churches emphasize unity amongst God’s children. To put it in a nut-shell: The Founder of the first Free evangelical Church in Germany, Hermann Heinrich Grafe (1818–1869), performed an ecclesiological balancing act in order to make the unity of the children of God visible: he has founded a particular Church as an expression of the Universal Church. The Free evangelical Churches came to life with a creed that preceded the ecumenical word of John 17:21. Their founders were aware of, that even a Protestant particular Church must continue to pursue the goal of reducing confessional egoism through prayer, personal encounters, common ministry, and serious theological discourses, and to discern the unity already existing in Christ for the world to believe. This goal remains, even though the numerical growth and confessional fragmentation of the one Church of Jesus Christ over the last two centuries make the visualization of their unity seem impossible. This article shows ecumenical chances and obstacles of the free-evangelical perspective on unity and identity, which are somewhat typical for ecumenical dialogues between free Churches and other Churches.